Blood pressure and renal outcomes after renal artery aneurysm intervention: Single-center experience and review of literature - Li, Siting; Li, Fangda; Liu, Zhili; Zeng, Rong; Ye, Wei; Shao, Jiang; Zheng, Yuehong (Frontiers in Cardiovascular Medicine, 2023)
Objective: To explore the results of hypertension improvement and renal function preservation after renal artery aneurysm (RAA) repair. Methods: This study retrospectively analyzed the change in blood pressure (BP) and renal outcomes of 59 RAA patients throughout either open or endovascular operations and follow-up at a large center. Patients were grouped according to the difference in their BP at the last follow-up vs. their baseline value. Logistic regression was conducted to explore risk factors for perioperative BP relief and long-term hypertension reonset. Previous studies of RAA with records of BP, blood creatinine level, or GFR/eGFR results are reviewed. Results: Hypertension was observed in 62.7% (37/59) of the patients included. Postoperative BP declined from 132.20±16.46/79.92±9.64 mmHg to 122.41±11.17/71.10±9.82 mmHg, while eGFR changed from 108.17±24.73 to 98.92±23.87 mL/min/1.73 m2. The median follow-up was 854 [IQR 1405] days. Both open and endovascular techniques significantly relieved hypertension and did not impair renal function much. Lower preoperative systolic BP (SBP) was significantly associated with hypertension relief (OR = 0.83, 95% CI 0.70-0.99). Among patients with normal BP after the operation, higher postoperative SBP was significantly associated with new-onset hypertension (OR = 1.14, 95% CI 1.01-1.29). Literature review indicated that renal function usually remained normal at follow-up, whereas relief of hypertension varied. Conclusion: Patients with lower preoperative SBP were likely to benefit more from the operation, while higher postoperative SBP indicated a higher chance of hypertension reonset. Creatinine level and eGFR generally remained stable regardless of operation type.